EVALUATION OF CLINICAL, ETIOLOGICAL AND EEG PROFILE OF NEONATAL SEIZURE - SARAL, SWATI; PATEL, DEEPAK KUMAR; AGRAWAL, ROOPA; RAJPOOT, SURJEET SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Neonatal seizure is a paroxysmal behavior caused by hyper-synchronous discharge of a group of neurons. Neonatal seizures are the most common overt manifestation of neurological dysfunction in the newborn. The electroencephalography (EEG) is an important tool in the evaluation of an infant with symptoms referable to the central nervous system. It provides an excellent and non-invasive method of assessing at risk newborns and of formulating a prognosis for long-term neurological outcome. Hence, this study was planned to evaluate clinical, etiological, and EEG profile of neonatal seizure and its corelation with developmental outcome. Methods: Prospective observational study was done among 71 cases of neonatal seizures patients admitted in Netaji Subhash Chandra Bose Medical College hospital from November 2014 to October 2015. All consecutive term and preterm neonates with documented seizure who were discharge from neonatal intensive care unit (NICU) with proper consent and counseling of parents were included in this study. Results: Total 71 newborns were enrolled, out of them 21% (n=15) were admitted within 24 h of birth, 42% (n=30) were admitted within 24–72 h, and 37% (n=26) newborn admitted at >72 h of birth. Total number of male included were 56% (n=40), while female were 44% (n=31). Out of 71 newborn, 60 newborn (84%) had subtle seizure, 4 (6%) had tonic seizures, 2 (3%) clonic seizure, and 5 (7%) had subtle with clonic seizure. In our study, most common causes of seizure were birth asphyxia 50% (n=36), meningitis 15% (n=11), and hypoglycemia 13% (n=9). Other common cause are hypocalcemia 8.5% (n=6), kernicterus 2.8% (n=2), and intraventricular hemorrhage 1.5% (n=1). Conclusion: In our study, we have found that preterm babies appear to have adverse neurodevelopmental outcome due to any brain insult occurred during neonatal period. Onset of seizure was found to be important predicting factor for developmental outcome. Frequency of seizure also has impact on developmental outcome, newborns who have single episode of seizure had good developmental outcome.